Navigating Turbulent Waters: Leading One Manitoba School in a Time of Crisis - Tamtik, Merli; Darazsi, Susan (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
The COVID-19 pandemic has profoundly changed the practice of school leadership, requiring greater flexibility, creativity, and innovation. Guided by institutional theory, this paper suggests that leadership adaptations are influenced by environmental pressures such as coercive (e.g., from governmental or regulatory agencies), mimetic (e.g., attempts to emulate best practices from other schools), and normative pressures (e.g., professional standards endorsed by professional societies or unions). By using a qualitative co-constructed autoethnographic approach (See Kempster & Iszatt-White, 2012), the paper presents the Covid-19 timeline in Manitoba, identifying stakeholders and associated environmental pressures. It also features the personal leadership adaptations experienced by a school principal (Susan). The findings suggest that coercive pressures are mostly associated with creativity and inventive leadership practices. Mimetic pressures may lead to copying behaviours, and normative pressures are associated with enhanced foundational knowledges, all depending on contextual factors. The findings also highlight the significant emotional and physical toll the pandemic has taken on school principals.